2016
DOI: 10.1159/000443493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Social Support, Quality of Life, and Body Image in Women with Breast Cancer

Abstract: Background: This study was aimed at comparing the quality of life, body image, and perceived social support in women with breast cancer surgery. Patients and Methods: Patients receiving breast-conserving surgery (BCS) (n = 72), mastectomy alone (n = 44), and mastectomy with breast reconstruction (n = 41) were evaluated using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30), the EORTC Breast Cancer Module (QLQ-BR23), the Body Image Scale (BIS) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
71
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 35 publications
24
71
0
2
Order By: Relevance
“…This finding is in agreement with the study done in Shanghai, China (27) in which high monthly income was associated with good quality of life and study done in Addis Ababa(23), in which those who have reported that they didn't have income, were less likely to have a good (unaffected) quality of life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is in agreement with the study done in Shanghai, China (27) in which high monthly income was associated with good quality of life and study done in Addis Ababa(23), in which those who have reported that they didn't have income, were less likely to have a good (unaffected) quality of life.…”
Section: Discussionsupporting
confidence: 92%
“…Study participants who were illiterate were nearly 3 times more likely to have affected QoL than those who were educated. This finding is supported with a study conducted in Shanghai, China (27) more educated breast cancer patients had improved quality of life. The similarity might be due to the fact that educated individuals can easily understand about the side effects of treatment and proper management of treatment side effects and usage so that they can even communicate easily with their health care providers to improve their quality of life.…”
Section: Discussionsupporting
confidence: 77%
“…Participants who were college graduated were about 3 times more likely to have good social support than those who were illiterate. This is in agreement with the study done in Italy and in New York (5,22). This similarity might be due to awareness about the importance of social support.…”
Section: Discussionsupporting
confidence: 92%
“…High monthly income in the current study was more likely to have brought a good quality of life. This nding is in agreement with the study done in Shanghai, China (22) high monthly income associated with good quality of life and study done in Addis Ababa (17) those who have reported that they didn't have income, less likely to have a good (unaffected) quality of life. This similarity might be due to can get necessary medication, food, self-care materials and can afford necessary things.…”
Section: Discussionsupporting
confidence: 92%
“…However, we only investigated the overall health assessments, and previous research also confirmed that in terms of these overall assessments there were only small differences between these groups [10,25]. This does not at all mean that these groups were equal with regard to specific symptoms or restrictions in functioning or body image [26]. According to our first hypothesis, cancer survivors assess the vignette characters as being markedly healthier, compared with the assessment of the general population.…”
Section: Discussionmentioning
confidence: 79%